Global and Personal Reflections on Training/Equipping for Cross-Cultural Ministry Today - Taylor, William David (Missiology, 2008)
This paper reflects personally on the author's journey in global mission, tracing his own diverse road through formal education and the later discovery of other modes of equipping for service. The pilgrimage makes a careful examination of cross-cultural mission and how we have historically created structures that train women and men for ministry — within their cultures or crossing them. Legitimate questions are raised in areas where formal training does not foster spiritual formation and community. The paper engages seven critical issues; presents the International Missionary Training Network, a component of the Mission Commission, World Evangelical Alliance; and concludes with four challenges.